Characterizing the Feeding Injury Caused by Phylloscelis rubra (Hemiptera: Dictyopharidae) to Cranberries. Issue 6 (25th December 2020) - Rodriguez-Saona, Cesar; Kyryczenko-Roth, Vera; Schiffhauer, Daniel; Firbas, Nicolas
Abstract: Due to changes in pest management practices, farmers' reports of severe feeding injury to cranberries, Vaccinium macrocarpon Aiton Ericales: Ericaceae, caused by the cranberry toad-bug, Phylloscelis rubra Ball, have increased in recent years in New Jersey (United States). Currently, however, limited information is available on the effects of P. rubra feeding or density of individuals needed to cause injury to cranberry vines and fruit. In 2015‒2017, we conducted studies to characterize injury to cranberry at a range of P. rubra densities by using cages in a screen-house and field, to establish a correlation between P. rubra density and crop injury in an open field experiment, and to measure the effects of P. rubra injury on the nutritional content (i.e., amounts of macro- and microelements) of cranberry vines. Phylloscelis rubra feeding on cranberry vines produced typical injury symptoms at relatively low densities (i.e., 2 individuals per vine in field cages or <10 individuals per sweep net sample in open fields), which included discolored (yellowish or reddish) or dead (brown) vines. This vine injury could lead to reductions in fruit mass and total fruit number. However, P. rubra injury to cranberry vines did not alter their nutritional composition. In general, this study highlights the ability of P. rubra to cause substantial injury to cranberry vines even when population densities were relatively low, which could result in declines in fruit production (quality and quantity). Therefore, infestations by P. rubra in cranberries must be considered when making pest management decisions in regions where this insect is present.